Monitoring and quantifying landscape changes using geoinformation technologies - Jasmy, Mohd Azzam; Mahamud, Mohd Amirul; Samat, Narimah; Hj. Mohd. Noor, Norzailawati (Malaysian Centre for Geospatial Data Infrastructure (MaCGDI), Ministry of Natural Resources and Environment (NRE), 2017)
Rapid urbanization has been major issues in many countries, especially in cities of the developing countries.This is mainly due to the migration of rural population to an urban area and natural population growth. A drastic increase of urban population has resulted in expansion of built-up areas which has encroached into an agricultural area at the urban fringe. Such phenomenon may alter the natural landscape of the affected areas impacting the livelihood of the community and disrupting the physical environment. This study, therefore, aims to explore and assess landscape changes due to the transformation of non built-up areas to urban activities. Taking, George Town conurbation, which experienced an expansion of the urban area as a case study, this study used satellite images from 2002 to 2014 to monitor land use and land cover changes. Landscape changes were analyzed using Patch Analyst software to identify landscape metric and quantify annual urban expansion index. The analysis revealed that significant changes in land use and land cover has taken place, especially after the year 2010 mainly caused by the spillover of the rapid development of Penang Island. The findings can assist planners and decision makers towards formulating an appropriate plan to manage urban transformation